Understanding the role of an educational model in developing knowledge of caring for older persons with dementia. (March 2016) - Prahl, Charlotte; Krook, Caroline; Fagerberg, Ingegerd
Abstract: Background: Statistics show that the number of older people in need of care is increasing worldwide, especially those with dementia. This implies demands on knowledge and competence among health care staff to care for them. In Sweden, Silviahemmet offers dementia care units the opportunity to become certified according to a special certification educational model. Silviahemmet provides educational programs for staff in dementia care and day care for person with dementia. All staff undergoes a systematic training course in dementia care. The aim of the study was to gain an understanding of how an educational model developed the perceived knowledge of staff caring for older persons with dementia in a nursing home. Method: A phenomenographical approach was used and qualitative interviews were carried out with 13 staff members in a nursing home. Findings: The main results show that staff perceives the importance of knowledge, working together and creating a sense of fellowship. The care of persons with dementia requires a special approach and adherence. Participating in the educational program made the staff realize and acknowledge their tacit knowledge and the importance of reflection-in-action together in the team. Conclusion: The results indicate the need for a common theoretical knowledge base and value system to achieve coherence in daily work. Highlights: Special certification educational model for the entire staff working with older persons with dementia. Underline the importance of knowledge about persons with the dementia. The need to approach and adhere the old person with dementia amongst all staff working with older persons with dementia.